Sukces Ruchu Palikota w świetle czynników możliwego sukcesu politycznego (Political Opportunity Structure) - Wojtasik, Waldemar (Political Preferences, 2012)
The aim of the presented text is an attempt to verify the most popular in the political science literature hypotheses about the emergence of new political movements, potential sourc- es of their electoral success and the prospects for a permanent presence on the political scene. The primary reference is a theoretical model of the Political Opportunity Structure, which is a complex description concept for the success sources of the new political movements. The context for the presented text are the parliamentary elections in 2011 and the success of a new political party - "Ruch Palikota".